2013
DOI: 10.1186/1471-2458-13-614
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cardiorespiratory fitness, physical activity, and obesity with metabolic syndrome in Hong Kong Chinese midlife women

Abstract: BackgroundSeveral studies have simultaneously examined physical activity (PA) and cardiorespiratory fitness (CRF) with metabolic syndrome (MS). However, the independent roles of both PA and CRF with MS are less firmly established. The combined contributions of PA and CRF with MS are less studied, particularly among Chinese women. There is uncertainty over the extent to which metabolically healthy but overweight/obese individuals have a higher CRF level.MethodsThe sample included 184 Chinese women aged 55 to 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…The finding has been well documented in numerous scientific studies in both sexes and in different age groups, especially as regards to cardiorespiratory fitness (CRF; (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)). Yu et al (17) showed greater associations of CRF with MetSy as compared with physical activity in middle-aged and elderly women. Low CRF has been recognized as a reliable predictor of cardiovascular morbidity and mortality as well as of all-cause mortality (18)(19)(20).…”
Section: Introductionmentioning
confidence: 73%
“…The finding has been well documented in numerous scientific studies in both sexes and in different age groups, especially as regards to cardiorespiratory fitness (CRF; (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)). Yu et al (17) showed greater associations of CRF with MetSy as compared with physical activity in middle-aged and elderly women. Low CRF has been recognized as a reliable predictor of cardiovascular morbidity and mortality as well as of all-cause mortality (18)(19)(20).…”
Section: Introductionmentioning
confidence: 73%
“…Many studies have compared the effects of PA on the development of MS (Das et al, 2012;Wagner et al, 2012;Yu et al, 2013). However, different methods have been used to assess PA in these studies, making it difficult to compare the results.…”
Section: Introductionmentioning
confidence: 98%
“…, meet the criteria of a high WC. 81,105,148 Recommendation 4: In accordance with previous MHO literature, 65,81,105,[148][149][150][151] we suggest to exclude WC among the criteria to be considered for MHO Question 5: How many MetS criteria should be met to be considered MHO?…”
mentioning
confidence: 99%